PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP HASIL BELAJAR SISWA PADA TEMA TUJUH KELAS V SDN 060938 MEDAN JOHOR - Emelia Sukses Ginting; Anton Sitepu; Dewi Anzelina; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of using the Cooperative Script learning models on students' learning outcomes in the theme of "Peristiwa Dalam Kehidupan" at grade V SDN 060938 Medan Johor Academic Year 2020/2021. The population in this study were all students at grade V of SDN 060939 Medan Johor in the Academic Year 2020/2021. The samples were 30 students selected by the boring sampling technique. The method in this study was descriptive-analytical. The results of this study indicated that the students' learning outcomes after using Cooperative Script model were categorized as excellent with an average of 83,86. The normality test obtained that the significance score of learning outcomes was Lcount > Ltable; meaning that 0.200 > 0.05. Based on the calculation, it was seen that the significance value of learning outcomes was normally distributed. In the correlations testing, the coefficient score was rcount ≥ rtable, in which 0.648 ≥ 0.349. Therefore, the Cooperative Script model strongly influenced the students' learning outcomes on the theme of "Peristiwa Dalam Kehidupan" at grade V of SDN 060938 Medan Johor. The result of the t-test showed that 4.498 >1.697; Ha was accepted. Thus, there was a positive influence and significant effect in using the Cooperative Script learning models on students' learning outcomes on the theme of"Peristiwa Dalam Kehidupan" at grade V of SDN 060938 Medan Johor Academic Year 2020/2021.